Terça Negra no Recife: narrativas sobre dança, música, espiritualidade e sagrado. - Prazeres, Maria Lúcia Gomes dos (2019)
The Terça Negra Project is one of the largest political-cultural events held by the Unified Negro Movement of Pernambuco - MNU, declared as the main strategy to combat racism and all forms of discrimination. The research project was created with the purpose of analyzing in the narratives of female leaders of Afoxé Alafin Oyó, Bloco Afro Raízes de Quilombo and Maracatu Leão Coroado, the relationship they establish between dance, music and living with spirituality and sacred. As specific objectives: 1) To raise the history of the Black Tuesday Project, starting from the memory of the founders, members of cultural groups, militants of the black movement and goers; 2) To observe ways of transferring elements of the African world view, with a view to the recognition of black identity and coexistence in the middle of racial memory; 3) Transcribe implicit speech and underlying dance and music presentations of the three groups. 4) To analyze, in the practices of female leaderships, a relationship between dance and music in living with spirituality and the sacred. The oral history was used as a methodological principle and the history of life as a genre adopted to capture information and narrative grounds, Meihy (2011). It was defined by four basic theoretical references, that similar to a web, approach Afro-Brazilian civilizational values, that intersect in a circular and constant way, giving meaning to the cultural matrix implied in the specific objectives: Sodré (2002) treats the territoriality from the where dance and music are seen as the center of communication and affirmation of a black identity, a principle that materializes the civilizing values of corporeity in dialogue with musicality and dance, in the construction of an image that allows both perception of itself in the other, as of the other in the movements made; Luz (2013) deals with African traditions in Brazil, values and languages, considering that each individual configures itself as a place, a territory, at once singular and social, always invested with the ancestral desire for continuity of the species, a principle that materializes the civilizational values of orality in dialogue with memory, which favor the transcription of the implicit discourse and underlying the presentations in dance and music; Augras (2008), bases the sacredness lived in the daily life of the Yabás through the African religious heritage, which proclaims the existence of the divinity in man and at the same time outside it and is strengthened by the values of religiosity in dialogue with the vital energy; Berkenbrock (2012) presents the way the Yoruba people understand the composition of the universe, AIYE AND ORUM forces that make possible the existence, both in the material world and in the transcendent, supernatural, unlimited world, that safeguard the three fundamental principles IWÁ - which makes the existence of the atmosphere and the breathing, AXÉ - that allows the unfolding of the dynamics of accomplishment, ABÁ - force that accompanies the AXÉ, giving objectivity to the direction to be followed and that is represented by the civilizing value of the territoriality in dialogue with the circularity , acting as an element of connection between the different knowledge and lived. Based on this guiding base, we analyze the narratives of the interviewees and we conclude that: a) the motivation of the interviewees to join the Terça Negra project is related to the discovery and appropriation of their black identity and their engagement in the militancy of policies racial; b) the social, political, cultural and religious changes and gains mobilized from Terça Negra are associated with the understanding of the African world view, materialized in the symbolic configuration of a web, that interconnects activities lived between people and groups that integrated the project.